Case Report: Glomeruloid hemangioma in external jugular vein - Peng, Guiping; Ju, Yawen; Dai, Miao (Frontiers in Surgery, 2025)
IntroductionGlomerular hemangioma is a rare vascular tumor characterized by capillary loops that resemble glomeruli within dilated vascular spaces. While primarily reported in the skin and soft tissues, its occurrence in the external jugular vein is extremely unusual. We present a case of a 32-year-old male with a glomeruloid hemangioma located in the left external jugular vein.Case presentationThe patient presented with a small, non-tender, non-pulsatile subcutaneous nodule on the left side of the neck. There were no associated symptoms such as skin redness, swelling, or systemic signs like fever. The patient's medical history was unremarkable, with no hypertension, diabetes, or other significant conditions. Routine laboratory tests, including blood counts, electrolytes, coagulation profile, thyroid hormones, and tumor markers, were all within normal ranges. Imaging studies, including neck computed tomography, chest x-ray, and ultrasound, were performed. Ultrasound revealed a well-defined mass within the left external jugular vein with abundant blood flow and a detectable arterial blood flow spectrum. The patient underwent surgical excision of the mass, followed by histopathological examination. Ultrasound imaging showed a mass measuring 8.6 mm × 5.3 mm within the left external jugular vein, slightly hyperechoic to surrounding muscle tissue, with clear borders and regular shape. Color Doppler imaging detected abundant blood flow, indicating a vascular lesion. Histopathological analysis of the excised mass revealed capillary loops within a dilated vascular lumen, resembling glomerular structures. These findings confirmed the diagnosis of glomeruloid hemangioma.ConclusionThis case highlights a rare presentation of glomeruloid hemangioma in the external jugular vein, emphasizing the importance of considering vascular tumors in the differential diagnosis of subcutaneous neck masses. Surgical resection was successful, and histopathology provided a definitive diagnosis. This case adds to the limited reports of glomeruloid hemangiomas, particularly in atypical locations, expanding the understanding of its clinical manifestations and diagnostic approach.